HUBUNGAN KEWENANGAN ANTARA PEMERINTAH PUSAT DENGAN PEMERINTAH DAERAH DALAM PELAKSANAAN PROGRAM/KEGIATAN ALOKASI DANA CUKAI HASIL TEMBAKAU - Insana Meliya Dwi Cipta Aprila Sari (Universitas Airlangga, 2012)
Implementation of The allocation of Profit-Sharing Fund of Tobacco-Product Duty (DBH-CHT) policy is a concurrent governmental affair. To some extent, it is mutually carried out by central government and local government, However, there are some components that exclusively become the authority of central government whereas the other ones are under the authority of provincial/regency/town government. Governmental affairs under the authority of provincial and regency/town governments are based on the principles of externality, accountability, and efficiency. Such affairs consist of compulsory affairs and optional ones.Key words: Profit-Sharing Fund of Tobacco-Product Duty, concurrent governmental affair, the authority of central government, the authority of provincial/regency/town government.